Factors Influencing Consumer Purchase Behavior of Saudi Dates - Almushaiti , Mohammad (American Journal of Business Science Philosophy, 2025)
This study examines the factors influencing consumer behavior toward Saudi dates, focusing on the roles of hedonic values, utilitarian values, purchase intention, and actual purchase behavior. A cross-sectional study design was employed, with data collected through an online survey from 271 consumers who include dates as part of their dietary plan. The questionnaire, translated into Arabic, was pilot-tested with 35 participants to ensure the validity and reliability of the measurement scales. Data analysis was conducted using structural equation modeling to explore the relationships between the constructs. The findings reveal that both hedonic values and utilitarian values significantly influence purchase intention, which in turn strongly predicts actual purchase behavior. The study demonstrates that consumers who derive pleasure and practical benefits from Saudi dates are more likely to intend to purchase them, and these intentions strongly translate into actual purchasing behavior. Additionally, the mediating role of purchase intention highlights its importance in linking hedonic and utilitarian values to actual behavior. By addressing both emotional and practical aspects of consumer behavior, businesses can create compelling marketing strategies that enhance purchase intentions and drive actual sales.